Bacterial Infection and Immune Responses in Lutzomyia longipalpis Sand Fly Larvae Midgut. - Matthew Heerman; Ju-Lin Weng; Ivy Hurwitz; Ravi Durvasula; Marcelo Ramalho-Ortigao (Public Library of Science (PLoS), 2015)
The midgut microbial community in insect vectors of disease is crucial for an effective immune response against infection with various human and animal pathogens. Depending on the aspects of their development, insects can acquire microbes present in soil, water, and plants. Sand flies are major vectors of leishmaniasis, and shown to harbor a wide variety of Gram-negative and Gram-positive bacteria. Sand fly larval stages acquire microorganisms from the soil, and the abundance and distribution of these microorganisms may vary depending on the sand fly species or the breeding site. Here, we assess the distribution of two bacteria commonly found within the gut of sand flies, Pantoea agglomerans and Bacillus subtilis. We demonstrate that these bacteria are able to differentially infect the larval digestive tract, and regulate the immune response in sand fly larvae. Moreover, bacterial distribution, and likely the ability to colonize the gut, is driven, at least in part, by a gradient of pH present in the gut.